2020
DOI: 10.1055/s-0040-1701459
|View full text |Cite
|
Sign up to set email alerts
|

Is Surgical Treatment an Option for Locally Advanced Cervical Cancer in the Presence of Central Residual Tumor after Chemoradiotherapy?

Abstract: Objective To evaluate the outcomes of surgical treatment in patients with chemoradiotherapy (CRT)-resistant and locally advanced cervical cancer (LACC). Methods Patients with LACC who underwent surgery due to resistance to CRT between 2005 and 2015 were reviewed retrospectively. Disease-free survival (DFS) and overall survival (OS) related factors were analyzed. Results A total of 23 patients were included in the study and the median age was 51 years old. A total of 14 patients (60.8%) expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Pervin et al was the only series to show no positive margins at the final pathological evaluation ( Table 3 ) [ 21 ]. Contrarily, Topuz et al documented a higher rate of positive margins (43.5%) after SS, but in this series, 17 patients (74%) had undergone a simple hysterectomy [ 22 ].…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…Pervin et al was the only series to show no positive margins at the final pathological evaluation ( Table 3 ) [ 21 ]. Contrarily, Topuz et al documented a higher rate of positive margins (43.5%) after SS, but in this series, 17 patients (74%) had undergone a simple hysterectomy [ 22 ].…”
Section: Resultsmentioning
confidence: 90%
“…Fifty-one articles were evaluated for eligibility after abstract and title screening. Finally, 11 studies were included in the systematic review [ 9 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. No additional studies were identified by checking the reference lists.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations